2015
DOI: 10.3389/fpsyg.2015.01210
|View full text |Cite
|
Sign up to set email alerts
|

Parent-infant interactions in families with women diagnosed with postnatal depression: a longitudinal study on the effects of a psychodynamic treatment

Abstract: Background: Several studies have shown a connection between mothers with postnatal depression (PND) and emotional-behavioral problems in their children. Mothers’ psychopathology may impair interactional patterns with children and these outcomes can be influenced by father’s psychopathological symptoms. The primary aim of the study was to assess over time parent-infant interaction in families where mothers have experienced PND and have received psychological treatment during the child’s first year of life consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Moreover, it has been found that the interaction of maternal depression and early maternal experiences of neglect and emotional abuse, predicted maladaptive scores on mothers' SVIA subscale affective state of the dyad. This result underlined the role of maternal psychological functioning on the quality of mother-infant and father-infant interactions (Tambelli, Cimino, Cerniglia & Ballarotto, 2015). As regard to fathers, data analyses found that paternal anxiety influenced child's food refusal during feeding, coherent with Ramchandani's study (2013).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, it has been found that the interaction of maternal depression and early maternal experiences of neglect and emotional abuse, predicted maladaptive scores on mothers' SVIA subscale affective state of the dyad. This result underlined the role of maternal psychological functioning on the quality of mother-infant and father-infant interactions (Tambelli, Cimino, Cerniglia & Ballarotto, 2015). As regard to fathers, data analyses found that paternal anxiety influenced child's food refusal during feeding, coherent with Ramchandani's study (2013).…”
Section: Discussionsupporting
confidence: 79%
“…The current findings add to this body of literature and suggest that parental empathy may be a key target for parenting interventions. Parenting behavior in parents with depression can be positively impacted by appropriate intervention [77,78]. Emphasizing empathy for one's own child may be particularly impactful for parents at risk for more negative parenting behaviors such as those with depression or postpartum depression, and might also be beneficial if incorporated into broader programs of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In total, the study contacted 3,812 families with the general aim of an assessment of need, with the possibility of intervention offered to all families only after that. The intervention program was offered to all families in need and was designed to include Home Visiting (Lyons‐Ruth et al., 2006; Olds et al., ; Tambelli, Cerniglia, Cimino, & Ballarotto, ); Parent Counselling (Holden et al., ; Murray et al., ); and Psychological Support with Video‐feedback Intervention (Downing, ; Stein, Woolley, Cooper, et al, ). One session of video‐feedback regarding the parent–infant interaction during feeding (with trained psychologists) was guaranteed to all families.…”
Section: Methodsmentioning
confidence: 99%